2021
DOI: 10.1038/s41598-021-91131-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between male and female breast cancer survival using propensity score matching analysis

Abstract: Male breast cancer (MBC) is a rare disease. The few studies on MBC reported conflicting data regarding survival outcomes compared to women. This study has two objectives: to describe the characteristics of a single-cohort of MBC and to compare overall survival (OS) and disease-free survival (DFS) between men and women using the propensity score matching (PSM) analysis. We considered MBC patients (n = 40) diagnosed between January 2004 and May 2019. Clinical, pathological, oncological and follow-up data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
3
11
1
Order By: Relevance
“…Male breast cancer is rare and is often diagnosed at an older age and later stage than female breast cancer, possibly influencing our results. 22 Previous studies are in line with our data and found small, if any, sex differences in association between VTE and cancer. A large registry-based study of patients with cancer reported higher multivariable adjusted risk of hospital-associated VTE in women (4.3%) compared with men (4.0%), giving an OR of 1.14 (95% CI 1.12-1.16).…”
Section: Discussionsupporting
confidence: 93%
“…Male breast cancer is rare and is often diagnosed at an older age and later stage than female breast cancer, possibly influencing our results. 22 Previous studies are in line with our data and found small, if any, sex differences in association between VTE and cancer. A large registry-based study of patients with cancer reported higher multivariable adjusted risk of hospital-associated VTE in women (4.3%) compared with men (4.0%), giving an OR of 1.14 (95% CI 1.12-1.16).…”
Section: Discussionsupporting
confidence: 93%
“…The rate of diagnosis of stage III and de novo stage IV disease was similar between men and women. In addition, stage-based OS for this cohort was similar to those found in the literature for male breast cancer, with stage IV having the worst clinical outcomes and ductal carcinoma in situ (DCIS) having the best [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 68%
“…Both older age and stage IV disease have been shown to decrease survival in male breast cancer populations [ 22 , 24 , 25 , 26 ]. Likewise, similar to females, lymph node-positive disease has been reported to be associated with inferior outcomes [ 23 , 25 ]. Poor performance status is known to be an important prognostic factor and, especially in advanced-stage disease, has been associated with inferior outcomes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every patient signed an informed consent for data unspecified use and the local ethical committee approved the anonymously data use, according to our legislation (GDPR 679/2016, Par.26) [ 11 ].…”
Section: Methodsmentioning
confidence: 99%